Sistem Kasir dan Pembukuan di Toko Bangunan "Murah" dan Penyewaan Sound System "Kurnia" - Ahmad Zaini, Bilal Jalali, Yogiek Indra Kurniawan, S.T.,M.T (2017)
Building stores or can be abbreviated as TB. "Murah" and Rental Sound System "Kurnia" are two different business sectors, TB. "Murah" is a line of business, while sales of building materials Hire Sound System "Kurnia" is engaged in the rental of sound system equipment. Both business areas are included in the management of the same. Basically TB. "Murah" and Sound System "Kurnia" do not have a proper accounting system, so that employees and owners are still difficulties in recording and information buying or selling, leasing and inventory. Based on these problems the author makes a cashier and accounting system with a web-based observational methods to obtain data in the form of master data and business rules that apply in the shop building "Murah" and Rental Sound System "Kurnia". In this system, there are four user comprising Admin TB. "Murah", Admin "Kurnia" Sound System, employees and owners. In this system there is a table of input and transaction processing results are stored in a MySQL database and PHP run so as to produce useful information. In the cashier and accounting systems are also monthly reports and the facility to print a proof of the transaction. The results of the implementation of the draft was tested by the method BlackBox and improvements that produce functioning in accordance with the design objectives.